Effective and safe surgery for keratinocyte skin cancer in the elderly over 80 years of age: a single-institution retrospective study of 345 patients over one year - Luca D. Fontana; Clara Richter; Ramon Lang; Christian Greis; Jürg Hafner (Journal of Dermatological Treatment)
Objectives As life expectancy rises and the population continues to age, physicians will be faced with an increasing number of elderly patients with keratinocyte cancer (KC). This study aims to better characterize KC surgery in patients over 80 years of age, with a particular focus on the incidence of postoperative complications.Methods A retrospective study was conducted on all patients aged 80 years and older who underwent surgery for KC at the University Hospital of Zurich in 2022. Data were collected from operative and postoperative notes within six months after surgery.Results A total of 565 tumors were removed from 345 patients, consisting mainly of basal cell carcinoma (46.5%) and squamous cell carcinoma (45.8%), including 24.2% clinically large tumors (>2 cm in diameter). A total of 26 complications were recorded, resulting in an overall complication rate of4.6%. Only one patient with a hematoma required surgical revision under local anaesthesia. Four cases of hemorrhage were solved by bed side ligations under local anaesthesia. Of the 26 recorded complications, 15 (58%) concerned wound dehiscence, requiring no further measures. The use of novel oral anticoagulants, lower extremity location, surgical specimen size >2 cm2, and flap repair were found to be independent risk factors associated with a statistically higher incidence of complications.Conclusions This study demonstrated that dermatologic surgery adapted to the geriatric population is relatively safe and effective, even for larger KC of several centimeters in diameter.